Effect of Work Place Support (WPS) on Personal Life Interference Work (PLIW) - Chatra, Admiral (CV. Lenggogeni Data Publishing, 2023)
The purpose of this study was to analyze how the effect of Work Place Support (WPS) on Personal Life Interference Work (PLIW) at PT. State Savings Bank (Persero) Tbk. Branch office. This type of research is descriptive exploratory using quantitative and qualitative methods. The quantitative method descriptive analysis in this study was divided into two, namely, univariate descriptive analysis and bivariate descriptive analysis. The results of this study are that Work Place Support (WPS) has a negative and significant effect on work interference with personal life or Work Life Interference Personal Life (WIPL) at PT. BANK TABUNGAN NEGARA (PERSERO) TBK KANTOR CABANG PADANG.. Abstrak Tujuan penelitian ini adalah untuk menganalisis Bagaimanakah pengaruh Work Place Support (WPS) terhadap Personal Life Interference Work (PLIW) di PT. Bank Tabungan Negara (Persero) Tbk. Kantor Cabang. Jenis penelitan ini adalah deskriptif eksploratif dengan menggunakan metode kuantitatif dan kualitatif. Analisa deskriprif metode kuantitatif dalam penelitian ini dibagi atas dua yaitu, analisis deskriptif univariat dan deskriptif bivariat. Hasil penelitian ini menunjukkan bahwa dukungan tempat kerja atau Work Place Support (WPS) berpengaruh negatif dan signifikan terhadap gangguan pekerjaan kepada kehidupan pribadi atau Work Life Interference Personnal Life (WIPL) di PT. BANK TABUNGAN NEGARA (PERSERO) TBK KANTOR CABANG PADANG.